An ontologic agent-based model of recreational polydrug use: SimUse. (2015) - Lamy, FranÁ§ois; Bossomaier, Terry; Perez, Pascal
SimUse is an ontology-based social simulation model aiming at reproducing trajectories of recreational poly-drug users. To describe and capture the complexity of this phenomenon, we bring together empirical evidence from ethnography with theoretical constructs from sociology and neuroscience into an agent-based model. After reviewing the context of recreational poly-substance use and justifying our approach, this paper describes the multi-layered structure of the simulation and details some of the key aspects of SimUse. We illustrate the capacity of SimUse to reproduce neurophysiological reactions to substance use and to explore 'what-if?' scenarios related to drug use.